Physician Burnout Scale: A Reliability and Validity Study: Physician Burnout Scale - Selvi, Huseyin; Toros, Turhan; Ozdemir, Asena Ayca; Bashan, Ibrahim (Progress in Nutrition, 2022)
Study Objectives: Although occupational burnout is experienced at different levels in different professions, it is an important problem affecting individuals’ quality of life and work efficiency. While burnout exists in almost every profession, it is more common in professions that require intensive physical and mental work and constant interaction with people such as medicine. There is no measurement tool developed solely for physicians which can reliably and validly measure physicians’ burnout levels in Turkey. This study aimed to present a scale developed directly for physicians on physician samples that can measure their burnout levels reliably and validly. Methods: Data were collected from a total of 479 physicians. The KMO value calculated to determine the suitability of the data for factor analysis was found to be 0.944. The chi-square statistics calculated as a result of the Barlett test were also significant (chi-square = 20381.76, p